Multifocal Hurthle cell (oxyphilic) variant of papillary thyroid carcinoma associated with Hashimoto`s thyroiditis: A case report - Qerimi, Adelina; Janevska, Vesna; Ognenoska-Jankovska, Biljana; Stojkoska, Elena; Spirovski, Zoran; Basheska, Neli (Macedonian Association of Pathology, 2016)
Objective: Oxyphilic (Hurthle cell) variant of papillary thyroid carcinoma (OVPTC) is a rare subtype accounting for 1-11% of all cases of papillary thyroid carcinomas (PTCs). The clinicopathological features and biological behavior of OVPTC have not yet been thoroughly characterized. We present a case of multifocal OVPTC with concurrent Hashimoto`s thyroiditis. Material and Methods: A 51-year-old female patient with multinodular goiter underwent a fine-needle aspiration biopsy which was reported as negative, followed by a subtotal thyroidectomy procedure. Results: The surgically obtained material consisted of two oval fragments designated as right and left thyroid lobe with the largest diameter of 5 cm and 4.5 cm, respectively. Grossly, on the cut section of the left lobe two well-circumscribed, white to grey-tanned foci with the largest diameter of 1.3 cm and 0.6 cm, respectively, were found. Microscopically, in a background of Hashimoto`s thyroiditis, the two foci revealed a neoplasm with predominantly insular growth pattern and focally follicular or papillary structures composed of large polygonal cells with abundant eosinophilic granular cytoplasm and optically clear nuclei with the characteristic intranuclear pseudoinclusions and nuclear grooves. Psammoma bodies and areas of calcification were also present. Mitoses were rare and no vascular or capsular invasion was encountered. Immunohistochemically, tumor cells showed diffuse positivity for low-molecular-weight cytokeratin and cytokeratin 19 and focal positivity for thyroid transcription factor-1. Conclusions: This case confirms that although OVPTC remains controversial, it usually displays the morphological and immunohistochemical features of the classical type of PTC, which can aid in avoiding the diagnostic pitfalls in distinguishing this subtype of PTC from other benign or malignant Hurthle cell lesions.
Proceeding & Abstracts of the 2nd Macedonian Congress of Pathology with International Participation, September 1-4, 2016, Ohrid, Macedonia, 2016:133.
Keywords: thyroid; papillary carcinoma; Hurthle cell variant; Hashimoto`s thyroiditis; pathology; immunohistochemistry